Actant Patterns of the Artistic World - Oleinikova, Galina (Journal of Danubian Studies and Research, 2023)
At present, in studies devoted to the literary text, the latter is considered not from a historical, bibliographic or psychological point of view, but as a phenomenon of language from a formal and semantic point of view. The sphere of interest of textual scholars is the various language levels and linguistic features of the text, which are primarily related to the interdisciplinary direction of all scientific knowledge. The fact that a text is not limited to one and only one correct interpretation has led scholars to the conclusion that a text is not just a linguistic unit. It is a complex system, and, like any system in nature, it should be studied taking into account internal and intersystemic interrelationships. This has led to the emergence of related sciences, the subject of which is the text as a means of language communication. Among the relatively new areas in the study of text are functional stylistics, linguistic stylistics, and text linguistics, which study the structure of "text - language communication," communication between the author and the reader, between the reader and the main characters or actants of a fiction.